Water sorption and hydration in spray-dried milk protein powders: Selected physicochemical properties. (30th January 2020) - Maidannyk, Valentyn; McSweeney, David J.; Hogan, Sean A.; Miao, Song; Montgomery, Sharon; Auty, Mark A.E.; McCarthy, Noel A.
Highlights: Powder water absorption rates were determined at different relative humidity. High protein powders absorbed more water compered to low protein systems. Water diffusion rates occurred slower in powders with high protein content. Increasing relative humidity reduced powder particle strength. Lactose crystallization occurred in low protein powders at high humidity. Abstract: Low and high protein dairy powders are prone to caking and sticking and can also be highly insoluble; with powder storage conditions an important factor responsible for such issues. The aim of this study focused on the bulk and surface properties of anhydrous and humidified spray-dried milk protein concentrate (MPC) powders (protein content ~40, 50, 60, 70 or 80%, w/w). Water sorption isotherms, polarized light and scanning electron micrographs showed crystallized lactose in low protein powders at high water activities. High protein systems demonstrated increased bulk diffusion coefficients compared to low protein systems. Glass transition temperatures, α-relaxation temperatures and structural strength significantly decreased with water uptake. CLSM measurements showed that humidified systems have slower real time water diffusion compared to anhydrous systems. Overall, the rate of water diffusion was higher for low protein powders but high protein powders absorbed higher levels of water under high humidity conditions.